Differential expression of Hz-1 baculovirus genes during productive and persistent viral infections. - Chao, Y C (1992)
Hz-1 viral RNA transcription was studied during productive and persistent infections. The RNAs were localized to 10- to 30-kb regions within the viral genome, and the timing of their expression was determined. During productive infections, we detected 101 virus-specific transcripts that could be grouped into three categories by time of appearance. At 2 h postinoculation (p.i.), a total of 34 virus-specific transcripts were detected. An additional 51 and 16 virus-specific transcripts appeared between 4 and 6 h p.i. and at 8 h p.i., respectively. After 8 h, no new transcripts were found. Under conditions of persistent infection, we detected only one viral persistency-associated transcript (PAT1). The region of the viral DNA which encodes PAT1 was cloned. During productive infections, three transcripts were derived from this region. Each had the same polarity as PAT1. One of them was of the same size as PAT1 and had similar, if not identical, 3' and 5' ends. This report provides detailed and very useful information concerning sequentially expressed transcripts of the Hz-1 baculovirus.